2021
DOI: 10.3389/fmed.2021.668898
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Developing Rheumatoid Arthritis in Patients With Undifferentiated Arthritis and Inflammatory Arthralgia

Abstract: Currently, there is an increasing interest in treating patients at risk of rheumatoid arthritis (RA) to prevent the development of this chronic disease. In this sense, research has focused attention on the early identification of predictive factors of this disease. Autoantibodies and markers of systemic inflammation can be present before clinical arthritis and RA development. So, the phase of inflammatory arthralgia preceding clinical arthritis is an important part of the window of opportunity and, starting tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 161 publications
(226 reference statements)
0
7
0
1
Order By: Relevance
“…The risk of RA was shown to be reduced in individuals who consumed more fatty fish (>8 g fat/100 g fish) than in those who consumed less fatty fish (between 3 and 7 g fat/100 g fish) in a Danish prospective cohort study. Women who consumed more than 0.21 g/day of long-chain n-3 polyunsaturated fatty acids had a 35% decreased chance of having RA [14].…”
Section: Discussionmentioning
confidence: 98%
“…The risk of RA was shown to be reduced in individuals who consumed more fatty fish (>8 g fat/100 g fish) than in those who consumed less fatty fish (between 3 and 7 g fat/100 g fish) in a Danish prospective cohort study. Women who consumed more than 0.21 g/day of long-chain n-3 polyunsaturated fatty acids had a 35% decreased chance of having RA [14].…”
Section: Discussionmentioning
confidence: 98%
“…The Colombia-based study found thar anti-CarP antibodies are more often observed in FDRs than healthy controls ( 117 ). It is important, however, the note that other studies did not find that this AMPA’s presence added additional risk for developing RA ( 115 ).…”
Section: Other Prospective Cohort Studies Among First-degree Relativesmentioning
confidence: 94%
“…Subjects in this cross-sectional study were 18 years or older ( 114 ). This is a critical study population because the link between genetics, and RA development have been heavily considered due to the increased conversion to RA diagnosis among FDRs ( 115 ). Previous studies have estimated the increase in risk of developing RA to be approximately 4 times higher in FDRs of people diagnosed with RA than in individuals that are not FDRs ( 116 ).…”
Section: Other Prospective Cohort Studies Among First-degree Relativesmentioning
confidence: 99%
“…Risk factors for RA include smoking, silica exposure, disorders of periodontal and intestinal microbiota, etc. ( Novella-Navarro et al, 2021 ). The immune cells and inflammatory mediators associated with RA mainly include T cells, B cells, macrophages, monocytes, interleukins (ILs), tumor necrosis factor-α (TNF-α), etc.…”
Section: The Pathogenesis Of Rheumatoid Arthritismentioning
confidence: 99%